Application of Data Mining Techniques in Determining the Accuracy of the Models Predicting the Student Academic failure - Azadeh Fadavi; Keyvan Salehi; Ebrahim Khodaie; Ali Moghadamzadeh; Mohammad Javadipour (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2020)
Introduction: Student academic failure is one of the shortcomings of higher education system. A system with the ability to predict and prevent the academic failure can play a decisive role in enhancing the quality of education. The utilization of educational data mining is one of the most effective strategies in monitoring and improving the quality of education. This study aimed to compare different data mining techniques in order to determine the best prediction model.